DFT Study of Electronic Properties and Chemical Reactivity in copper cluster Hexaquis (mu2-Benzoate- O,O')-hexa-copper(I) - Chavez Serrano, Jean (2018)
MOFs (Metal-Organic Frameworks), are a new class of hybrid microporous materials defined as extended networks, formed by metal ions joined by covalent bonds coordinated with polyfunctional organic ligands, forming structures in 1D, 2D and 3D. This computational study evaluates the electronic properties and chemical reactivity of a section of the metal-organic network (MOFs) for copper with carboxylate ligands (benzoate) reported in the Cambridge Structural Database (CSD) called hexaquis copper cluster (m2-Benzoate). O, O ') - hexacobre (I), in order to explain the behavior of the active sites present in its structure. The calculation was made with the program Q-Chem 4.0, which is used for accurate predictions of molecular structures, reactivities and vibrational, electronic and NMR spectra, using the graphical interface of Spartan 14 version 1.1.4 and the hybrid density functional B3LYP and the base function 6-31G *.